Sinus pericranii, skull defects, and structural brain anomalies in TRAF7‐related disorder. Issue 14 (27th May 2020) - Accogli, Andrea; Scala, Marcello; Pavanello, Marco; Severino, Mariasavina; Gandolfo, Carlo; De Marco, Patrizia; Musacchia, Francesco; Torella, Annalaura; Pinelli, Michele; Nigro, Vincenzo; Capra, Valeria
Abstract: Background: Several somatic mutations in TRAF7 have been reported in cancers, whereas a few germline heterozygous mutations have been recently linked to a neurodevelopmental disorder, characterized by craniofacial dysmorphisms, congenital heart defects, and digital anomalies. Cases: We report two subjects harboring de novo heterozygous missense variants in TRAF7, namely the recurrent 1964G>A(p.Arg655Gln) and the novel missense c.1204C>G(p.Leu402Val) variants. In addition to the typical hallmarks of the TRAF7‐related disorder, both subjects presented with a recognizable "pear‐shaped" skull due to multiple craniosynostosis, sinus pericranii, skull base/cranio‐cervical junction anomalies, dysgyria, and inferior cerebellar vermis hypoplasia. Conclusions: Hence, we expand the genotypic and phenotypic spectrum of this neurodevelopmental disorder, discussing possible implications for clinical management of subjects with germline TRAF7 mutations.